Cognitive modeling of problems and methods of protecting territories from landslides - Galina V. Gorelova; Dmitry I. Katsko; Alexander I. Katsko (Мелиорация и гидротехника)
Purpose: to develop landslide process modeling methods at the pre-formal study stage. Materials and methods. The methodology development is based on the author's experience in designing landslide preventive measures, as well as the experience of assessing landslide haz-ard based on available data (visual observations, engineering surveys and regulatory docu-mentation). The theory of environmental engineering, systems approach and cognitive model-ing were used. Results and discussion. The ideology of cognitive modeling as a basis for pre-formal study of problems (causes) and methods of protecting territories from landslides is proposed and im-plemented. The cognitive map made it possible to solve the problem of identifying or match-ing the real landslide process and methods of protecting territories from landslides with their graphical representation in the form of concepts (graph vertices) and cause-and-effect rela-tionships between them (graph edges), which subsequently allows us to move on to formaliza-tion – the construction of mathematical models (Bayesian belief networks, simultaneous equa-tions systems, path analysis models, etc.). Scenarios for the development of complex situations associated with the imitation of the activity of one or more vertices of the cognitive map which makes it possible to answer the questions “what if ...” and thus provide support in mak-ing decisions on carrying out reclamation measures for landslide protection were obtained. Conclusions. The obtained cognitive models make it possible to carry out simulation modeling and obtain scenarios for the development of various complex situations. The results can be used in a decision support system for developing models of probabilistic landslide risk management during the formation and operation of engineering structures.